2018
DOI: 10.1177/2053168017749383
|View full text |Cite
|
Sign up to set email alerts
|

#NeverTrump: Why Republican members of Congress refused to support their party’s nominee in the 2016 presidential election

Abstract: In an election characterized by countless headlines, the refusal of Republicans to support their party's nominee was a constant topic of discussion in 2016. Our paper looks to explain why Republican members of Congress joined the socalled #NeverTrump movement. In the first part, we document the varied-and often contradictory-explanations of the #NeverTrump movement offered by journalists, pundits, and politicians during the campaign. We then categorize these popular explanations into four theoretical categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(24 reference statements)
2
5
0
Order By: Relevance
“…Notably, this contradicts the suggestion from some in the media that Trump’s presidency represents a war on the party’s establishment (CNN 2017; Washington Post 2017). Both results are consistent with the finding that conservative and establishment Republicans were more likely to endorse Trump in the 2016 campaign (Johnson, McCray, and Ragusa 2018).…”
Section: Member-level Findingssupporting
confidence: 89%
See 3 more Smart Citations
“…Notably, this contradicts the suggestion from some in the media that Trump’s presidency represents a war on the party’s establishment (CNN 2017; Washington Post 2017). Both results are consistent with the finding that conservative and establishment Republicans were more likely to endorse Trump in the 2016 campaign (Johnson, McCray, and Ragusa 2018).…”
Section: Member-level Findingssupporting
confidence: 89%
“…Because the model controls for a range of factors, gender seems to be a salient dimension vis-à-vis Trump’s presidency. We note that this effect is consistent with the finding that female Republicans were more likely to join the #NeverTrump movement in the 2016 campaign (Johnson, McCray, and Ragusa 2018). We do not find a significant effect on the Mormon variable, however.…”
Section: Member-level Findingssupporting
confidence: 89%
See 2 more Smart Citations
“…Noel ( 2016 ) turned this new interpretation into a compromise dimension, arguing that the second dimension captures the degree to which members of congress favor their ideology over the procedural demands of their party. Johnson, McCrary, and Ragusa ( 2018 ) also use second-dimension DW-NOMINATE scores to try and capture a populist or establishment vs. anti-establishment divide in the Republican Party. In his use of the second dimension to examine partisan warfare, Theriault ( 2013 ) found that negative scores seem to indicate members who are more anti-establishment and less willing to compromise.…”
Section: A Multidimensional Model Of Free Agencymentioning
confidence: 99%